2012
DOI: 10.1007/s10008-011-1637-8
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and characterization of blended solid polymer electrolyte 49% poly(methyl methacrylate)-grafted natural rubber:poly(methyl methacrylate)–lithium tetrafluoroborate

Abstract: The preparation and characterization of blended solid polymer electrolyte 49% poly(methyl methacrylate)-grafted natural rubber (MG49):poly(methyl methacrylate) (PMMA) (30:70) were carried out. The effect of lithium tetrafluoroborate (LiBF 4 ) concentration on the chemical interaction, structure, morphology, and room temperature conductivity of the electrolyte were investigated. The electrolyte samples with various weight percentages (wt. %) of LiBF 4 salt were prepared by solution casting technique and charact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 34 publications
(48 reference statements)
1
3
0
Order By: Relevance
“…The most probable reason for this behavior is the presence of interactions between Li + ions with the partially negative charges of oxygen atoms in the carbonyl functional groups. The same result also was reported in the recent publication of polymer host that contains carbonyl functional groups and lithium salt [10,14]. Figure 2 shows asymmetric stretching mode of ether functional group for PGMA, which is observed at 1146 cm −1 .…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…The most probable reason for this behavior is the presence of interactions between Li + ions with the partially negative charges of oxygen atoms in the carbonyl functional groups. The same result also was reported in the recent publication of polymer host that contains carbonyl functional groups and lithium salt [10,14]. Figure 2 shows asymmetric stretching mode of ether functional group for PGMA, which is observed at 1146 cm −1 .…”
Section: Resultssupporting
confidence: 86%
“…Previous studies reported that Li + tends to interact with the oxygen atoms, thus indirectly be transported through the segmental motion of polymer chains [13,14]. In addition, the lone pairs that were carried by those polar functional groups were believed to contribute to the effective salt solvation [10,11,14].…”
Section: Introductionmentioning
confidence: 99%
“…The application of those thermoplastics can be easily found in our daily life, including its application as electrolyte membrane. [1][2][3][4][5] However, as amorphous materials, these materials exhibit the poor mechanical properties, e.g. gel formed of PMMA.…”
Section: Introductionmentioning
confidence: 99%
“…2 The presence of this oxygen atom could hinder the migration of lithium ion in the blends due to the high chances of the coordinate bond formation between the oxygen atom and lithium ion. 5,23 The ionic conductivity value significantly decreased at PMMA 30 wt.% content, it could be due to the blend was immiscible and the phase separation occurred. This statement was supported by the temperature glass value at the 30 wt.% of PMMA in Figure 5.…”
mentioning
confidence: 98%